Technology Acceptance Model (TAM) in education / Dr. Baderisang Mohamed, Mohd. Sukor Md. Yusoff and Ira Syazwani Mohamad Marzuki - Mohamed, Baderisang; Md. Yusoff, Mohd. Sukor; Mohamad Marzuki, Ira Syazwani (Universiti Teknologi MARA, Kedah, 2022)
With the ever-increasing improvement of technology and its integration into the users' non-public and professional lives, the choice concerning the acceptance or rejection of the Technology Acceptance Model (TAM) remains an open question. Significantly, TAM is one of the popular and regular models that is used to learn about social mechanisms of technology adoption, which has changed from time to time. Originating from the psychological theory of reasoned action and the theory of planned behaviour, TAM has developed and emerged as a key model in understanding predictors of human conduct towards potential acceptance or rejection of the technology.